Business plan for Hilir-Living – residential rental service - Ismail, Muhammad Hulaimi (2022)
For years, tenants are renting houses directly from individual property owners on informal arrangement. What happened in this industry is, it is rarely that one can buy service from professional and reliable companies that guarantees protection and reasonable customer service level. For renters, this means they have to put up with inconveniences and even find themselves in dispute with homeowners—it is not what one can describe as a pleasant customer experience.